The effect of prolonged endurance exercise upon blood pressure regulation during a postexercise orthostatic challenge. Issue 10 (3rd November 2008) - Privett, S E; George, K P; Middleton, N; Whyte, G P; Cable, N T
Abstract : Objective: To investigate the regulation of blood pressure in response to an orthostatic challenge in athletes running a marathon. Methods: 10 experienced male runners (mean (SD) age 29 (4) years) were tested on the day prior to the 2004 London Marathon, and again immediately postrace (race time 210 (36) min). In addition, 6 of the subjects were retested 24 h postrace. During each examination, beat-to-beat systolic arterial blood pressure (SBP) and heart rate (HR) were measured, and stroke volume (SV), cardiac output (CO) and total peripheral resistance (TPR) were estimated via arterial transmural pressure waveforms during 3 min in a supine position and then during 3 min of upright, unsupported standing. Data were averaged over 20 s epochs, and the final 20 s of each posture were compared prerace and postrace via repeated measures 2-way ANOVA. Results: Prerace SBP in standing increased only moderately when compared with supine values (2 (9) mm Hg, NS). This was accompanied by an increase in HR (13 (7) beats/min, p<0.05), as well as a decrease in SV (16 (9) ml, p<0.05). However, there was little change in CO (−0.13 (0.97) litres/min, NS) or TPR (0.047 (0.280) medical units (MU), NS). Postrace SBP significantly decreased from supine to standing (−15 (20) mm Hg, p<0.05). The change in SBP was accompanied by an increase in HR (19 (6) beats/min, p<0.05) and a reduction in SV (26 (14) ml, p<0.05) and CO (−1.02 (1.39) litres/min, p = 0.05). Postrace there was no change in TPR (0.366 (0.607) MU, NS) upon standing. The orthostatic adjustments in SBP, HR and CO were greater than at prerace (p<0.05). The postrace orthostatic challenge resulted in only one subject experiencing presyncopal symptoms. At 24 h postrace, cardiovascular responses to an orthostatic challenge mirrored those at prerace. Conclusions: Following prolonged exercise, a fall in systolic blood pressure during orthostasis results from an inadequately compensated decrease in SV and resultant CO during standing.